Finance-growth nexus: evidence based on new measures of finance - Ibrahim, Saifuzzaman; Abdullahi, Abu Bakar; Wan Ngah, Wan Azman Saini; Abdul Rahman, Mazlina (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study examines the impact of financial development on economic growth using both the development of banking sector and the development of stock market as indicators of financial development. In order to reduce information loss, new measures of the banking sector and the stock market development are derived from various available measures via principal component analysis. Using the generalized method of moments (GMM) estimation technique on a 1988-2012 sample of 53 countries, the study reveals that the development in the banking sector and the stock market are both important to promote economic growth.